Gambaran Penatalaksanaan Pasien Syok Kardiogenik - Istiqamah, Istiqamah; Dwimartyono, Fendy; Apris, Muhammad Asrul (Universitas Pahlawan Tuanku Tambusai, 2024)
Tissue perfusion abnormalities may impair cell metabolism, leading to shock, a severe pathophysiological condition. Complete peripheral circulatory failure occurs under shock situations, leading to insufficient tissue perfusion. Hypoperfusion of end organs and mortality may result from shock-related low cardiac output, even in the presence of sufficient intravascular volume. Cardiogenic shock is associated with a relatively high mortality rate; around 22.4% of patients pass away within the first year. This research made use of a narrative review approach to its literature evaluation. According to this study's findings, which were derived from a survey of ten literatures, inotropic and vasopressor treatment is the norm for individuals experiencing cardiogenic shock. This study's findings suggest that inotropic and vasopressor medications are best employed as a bridge between treatments or as an initial line of defense in the fight for hemodynamic stability. Norepinephrine and dobutamine are the inotropic and vasopressor medicines of choice for the treatment of cardiogenic shock, according to many recent research and guidelines.